CONJUCTIONS: AN ATTEMPT AT IDENTIFYING THEIR ROLE IN SLOVENE COMPLEX SENTENCES (Philological Studies, 2019)
The article aims to present the meanings of conjunctions through their functions in different content relationships. It demonstrates the varying inter-dependence of conjunctions and predicators in coordination and subordination, especially drawing attention to the relationships between conjunctions of the same class and conjunctions within the same content relationship.
Keywords: conjunctions, syntactico-semantic relationships, conjunction and predicator inter- dependence, coordination, subordination